Orientalist’s Catalogue Making in 19thCentury: Research Perspective - Prof. Dr. Naseem Abbas Ahmar (Zaban-o-Adab, 2024)
Catalogue making is important component of reference research. The books in personal libraries are not only a source of interest and information for historians and researchers, but also reveal the intellectual and academic tendencies of individuals. In literary research, the importance of manuscripts compared to publications is twofold. Fort William College is also credited with cataloging making of the manuscripts in Urdu. In this field too, the remarkable work of the Orientalists comes to the fore. Important Orientalists in this regard are Charles Stewart, Springer and J. F. Blumhardt. In this article, an introduction to the cataloging of the above important Orientalists has been made the subject.